Identification of Iridoid Glucoside Transporters in Catharanthus roseus. (19th July 2017) - Larsen, Bo; Fuller, Victoria L.; Pollier, Jacob; Van Moerkercke, Alex; Schweizer, Fabian; Payne, Richard; Colinas, Maite; O'Connor, Sarah E.; Goossens, Alain; Halkier, Barbara A.
Abstract: Monoterpenoid indole alkaloids (MIAs) are plant defense compounds and high-value pharmaceuticals. Biosynthesis of the universal MIA precursor, secologanin, is organized between internal phloem-associated parenchyma (IPAP) and epidermis cells. Transporters for intercellular transport of proposed mobile pathway intermediates have remained elusive. Screening of an Arabidopsis thaliana transporter library expressed in Xenopus oocytes identified AtNPF2.9 as a putative iridoid glucoside importer. Eight orthologs were identified in Catharanthus roseus, of which three, CrNPF2.4, CrNPF2.5 and CrNPF2.6, were capable of transporting the iridoid glucosides 7-deoxyloganic acid, loganic acid, loganin and secologanin into oocytes. Based on enzyme expression data and transporter specificity, we propose that several enzymes of the biosynthetic pathway are present in both IPAP and epidermis cells, and that the three transporters are responsible for transporting not only loganic acid, as previously proposed, but multiple intermediates. Identification of the iridoid glucoside-transporting CrNPFs is an important step toward understanding the complex orchestration of the seco-iridioid pathway.